Rolling Bearing Dynamics Response and Parameter Sensitivity Analysis based on the Response Surface Method - Shi Jialian; Ma Xiaogang; Li Chang; Xie Kuiqiu (Jixie chuandong)
The dynamics model of rolling bearing of automotive engine bearing-rotor system is established and the nonlinear dynamics differential equation is derived. The numerical solution is obtained by MATLAB after nondimensionalization,the change rule of dynamic response of rolling bearing is obtained. The influence of variations in each parameter on the dynamics performance of rolling bearing is thoroughly considered based on the response surface method. With the displacement amplitude response at a moment of the steady state as the research object,the influence sensitivity of each parameter on the performance of the bearing system is given quantitatively. The response pattern of the bearing system is grasped,and the sensitivity of each parameter on the bearing system is clarified,the theoretical guidance for subsequent optimization analysis on the performance parameters of the bearing system is provided.